Gender, self-efficacy and personality traits as correlates of career choice of adolescents with hearing impairment in Oyo State, Nigeria (2014)
The study examined the relationship among gender, self-efficacy, personality traits and career choice among adolescents with hearing impairment in Oyo State, Nigeria. The descriptive survey research design was adopted in carrying out the study. The purposive sampling technique was used to select 100 male and female adolescents with hearing impairment from Durbar Grammar School, Oyo and Methodist Grammar School, (Deaf Unit), Bodija, Ibadan, Nigeria. A 30-item questionnaire was used to collect data for the study. Data were analyzed using Pearson Product Moment Correlation and Multiple Regression Analysis. Gender (r=.287, P<0.05), self-efficacy (r=.105, P<.05) and personality traits (r=.087, P<0.05) were positively correlated with career choice among adolescents with hearing impairment. Gender, self-efficacy and personality type significantly predicted the career choice of adolescents with hearing impairment (F(3,97) = 6.824, P<0.05) and contributed 74% of the total variance to the dependent variable. The relative contributions of the independent variables to career choice of adolescents with hearing impairment are as follows: Gender ((-.279), self- efficacy ((=.212) and personality traits ((=.045) respectively. Gender, self-efficacy and personality traits are important factors that enhanced career choice of adolescents with hearing impairment. Parents, teachers and rehabilitators should encourage adolescents with hearing impairment to come to term with their disabilities in order to choice careers that would make them to be economical independent.